Self Efficacy Meningkatkan Perilaku Pasien Dalam Latihan Mobilisasi Post Operasi ORIF Pada Ekstremitas Bawah - Ace sudrajat; Wartonah Wartonah; Eska Riyanti; Suzana Suzana (Jurnal Ilmu dan Teknologi Kesehatan, 2019)
Surgery for bone repositioning through internal fixation (Open Reduction Internal Fixation) is a medical action to improve the position of the fractured bone. The purpose of the ORIF action is to restore the function of bone movement and stabilization so that patients are expected to mobilize early after surgery. One of the treatment focuses on postoperative patients with ORIF is gradual exercise and activity. The purpose of the study was to determine the effect of self-efficacy of postoperative patients with ORIF in the exercise of lower extremity mobilization. The cross sectional research method that involving 80 respondents who had been carried out ORIF installation surgery in the orthopedic surgical treatment room. Data analysis using linear regression test, the results showing that there is a positive and significant effect of the patient's self-efficacy on lower limb mobilization exercises at p-value = 0.005 with the R square value = 0.495 which means that the effect of self-efficacy is moderate on post ORIF patient mobilization exercises. So in general it can be concluded that the effect of increasing patient efficacy will increase the behavior of lower limb mobilization exercises in lower limb patients.